NUTRICOSMETICS: ACTIVE INGREDIENTS AND CLINICAL BENEFITS BASED ON SCIENTIFIC EVIDENCE - M.A. HANNY FERRY FERNANDA (Universitas Negeri Surabaya, 2025)
Nutricosmetics are oral nutritional interventions designed to enhance skin health and aesthetics through internal biological mechanisms. The growing beauty-from-within trend has accelerated research on active compounds such as hydrolyzed collagen, oral hyaluronic acid, probiotics, and astaxanthin. This article synthesizes current scientific evidence by reviewing studies published between 2015 and 2025 retrieved from Scopus, PubMed, Web of Science, and ScienceDirect. Eight key publications, including meta-analyses, systematic reviews, and randomized controlled trials (RCTs), were evaluated to determine the clinical effectiveness of nutricosmetics on skin parameters. Hydrolyzed collagen demonstrates the strongest evidence base, with a meta-analysis of 26 RCTs ( 1,721 participants) reporting significant improvements in skin hydration and elasticity. Oral hyaluronic acid likewise shows benefits in hydration, elasticity, and wrinkle reduction, supported by findings from seven RCTs. Probiotic supplementation exhibits clinical efficacy in acne management via modulation of the gut–skin axis, while astaxanthin offers potential improvements in hydration and photoprotection, although current data remain limited. Variability in dosing, formulations, and study duration contributes to heterogeneity across trials. Overall, nutricosmetics present promising complementary strategies for enhancing skin hydration, elasticity, and age- related parameters. Standardized methodologies and long-term clinical trials are required to strengthen evidence- based recommendations.